Hot Topics in Burn Injuries - Pelin Kartal, Selda; Bayramgürler, Dilek (IntechOpen, 2018)
The aim of this book is to give readers a broad review of burn injuries, which may affect people from birth to death and can lead to high morbidity and mortality. The book consists of four sections and seven chapters. The first section consists of the introductory review chapter, which overviews the burn injuries. The second section includes chapter "Burn Etiology and Pathogenesis," which focuses on burn injuries and clinical findings. The third section consists of chapter "Controlling Inflammation in Burn Injury" and is devoted to the role of inflammatory response, which is fundamental to the healing process, while a prolonged inflammation may lead to scarring and fibrosis. The fourth section consists of four chapters as follows: "Therapeutic Effects of Conservative Treatments on Burn Scars," "Herbal Therapy for Burns and Burn Scars," "Platelet-Rich Plasma in Burn Treatment," and "Surgical Treatment of Burn Scars." The book is easy to read and includes hot topics on burn injury to enhance the reader's understanding and knowledge.